Uptake and translocation of magnetite (Fe3O4) nanoparticles and its impact on photosynthetic genes in barley (Hordeum vulgare L.). (July 2019) - Tombuloglu, Huseyin; Slimani, Yassine; Tombuloglu, Guzin; Almessiere, Munirah; Baykal, Abdulhadi
Abstract: This study investigates the fate and impact of iron oxide or magnetite (Fe3 O4, ∼13 nm in size) nanoparticles (NPs) in barley ( Hordeum vulgare L.), a common crop cultivated around the world. Barley seedlings were grown in hydroponic culture for three weeks to include NPs (125, 250, 500, and 1000 mg/L). Transmission electron microscopy (TEM) and vibrating sample magnetometer (VSM) techniques were used to assess their uptake and translocation. Photosynthesis marker genes were quantified by RT-qPCR. Results revealed that increasing doses of Fe3 O4 NPs were gradually enhanced the plant growth up to 500 mg/L, which promoted the fresh weight (FW) respectively ∼19% and ∼88% for leaf and root tissues than the ones for control. No phytotoxic effect was recorded even at high NPs doses. NPs inclusion increased some phenological parameters such as chlorophyll, total soluble protein, number of chloroplasts, and dry weight. High NPs doses dramatically reduced the catalase activity and hydrogen peroxide content, suggesting a possible function of NPs as nanozyme in vivo . TEM observations showed that Fe3 O4 NPs penetrated and internalized in the root cells. In leaves, they were mostly existed at the surrounding cell wall, suggesting their translocation from root to shoot without cellular penetration. Further analysis by using VSM confirmed the existence of Fe3 O4 NPs in leaves which result in dramatic alterations of the photosystem genes ( PetA, psaA, BCA and psbA ). In conclusion, barley plants uptake and translocate Fe3 O4 NPs, which promoted the plant growth probably due to the promoted gene expression and efficient photosynthetic activity. Highlights: Iron oxide (Fe3 O4, ∼13 nm) NPs are up-taken by roots and translocated to leaves. They enhanced the plant growth without phytotoxic effect. They were mostly existed at the surrounding cell wall without cellular penetration. High NPs doses reduced the hydrogen peroxide content, likely act as nanozyme. Expression of photosynthetic genes, petA and psaA were increased dramatically.